2022
DOI: 10.1159/000522547
|View full text |Cite
|
Sign up to set email alerts
|

Final Results of TACTICS: A Randomized, Prospective Trial Comparing Transarterial Chemoembolization Plus Sorafenib to Transarterial Chemoembolization Alone in Patients with Unresectable Hepatocellular Carcinoma

Abstract: Introduction Several clinical trials comparing the efficacy and safety of transarterial chemoembolisation (TACE) plus molecular-targeted agents versus TACE alone revealed no clinical benefits in progression-free survival (PFS) or overall survival (OS). Here, we report the final OS analysis from the TACTICS trial, which previously demonstrated significant improvement in PFS with TACE plus sorafenib in patients with unresectable hepatocellular carcinoma (HCC) (NCT01217034). Methods Patients with unresectable HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
91
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(94 citation statements)
references
References 34 publications
2
91
0
1
Order By: Relevance
“…However, since the TACTICS trial significantly prolonged the PFS, which was the primary endpoint, the OS result was anticipated, which was the coprimary endpoint. However, the final OS data made available during the ASCO-GI 2021 showed that patients treated with a combination of TACE plus sorafenib had an OS of 36.2 months (95% CI 30.5–44.1), while those with treated with TACE alone had an OS of 30.8 months (95% CI 23.5–40.8, HR 0.86, 95% CI 0.61–1.22; P = 0.40); therefore, the results were considered negative [ 65 ]. The factors contributing to this negative result were as follows: (1) 156 patients set as Phase 2 trial were underpowered to meet the OS endpoint and (2) 76.3% of patients in the TACE alone group received post-treatment (50% of whom were treated with sorafenib), resulting in an extremely long post-progression survival (PPS: 17.3 months).…”
Section: Role Of Systemic Therapy In Intermediate Stage Hccmentioning
confidence: 99%
See 3 more Smart Citations
“…However, since the TACTICS trial significantly prolonged the PFS, which was the primary endpoint, the OS result was anticipated, which was the coprimary endpoint. However, the final OS data made available during the ASCO-GI 2021 showed that patients treated with a combination of TACE plus sorafenib had an OS of 36.2 months (95% CI 30.5–44.1), while those with treated with TACE alone had an OS of 30.8 months (95% CI 23.5–40.8, HR 0.86, 95% CI 0.61–1.22; P = 0.40); therefore, the results were considered negative [ 65 ]. The factors contributing to this negative result were as follows: (1) 156 patients set as Phase 2 trial were underpowered to meet the OS endpoint and (2) 76.3% of patients in the TACE alone group received post-treatment (50% of whom were treated with sorafenib), resulting in an extremely long post-progression survival (PPS: 17.3 months).…”
Section: Role Of Systemic Therapy In Intermediate Stage Hccmentioning
confidence: 99%
“…The factors contributing to this negative result were as follows: (1) 156 patients set as Phase 2 trial were underpowered to meet the OS endpoint and (2) 76.3% of patients in the TACE alone group received post-treatment (50% of whom were treated with sorafenib), resulting in an extremely long post-progression survival (PPS: 17.3 months). However, considering that the OS results were negative despite the longest OS (36.2 months) and ΔOS (5.4 months) among previous combination trials of TACE and a molecular targeted agent, The results clearly showed it is no longer possible to use OS as the primary endpoint in future trials of TACE plus systemic therapy in an era with various many effective post-treatment options [ 65 ].…”
Section: Role Of Systemic Therapy In Intermediate Stage Hccmentioning
confidence: 99%
See 2 more Smart Citations
“… 91–94 The complexity of study design issues has been extensively reviewed elsewhere to get insight from previous trials. 22 , 95 Most trials incorporated more detailed definition of patient characteristics (e.g., ALBI grade, 96 , 97 HAP score, 6 , 98 , 99 AFP level 100 ) and treatment patterns (e.g., geographic regions or study sites, drug-eluting beads versus conventional TACE) in the hope of better stratification for this very heterogeneous patient population. Several trials incorporated TACE-specific endpoints, such as time to TACE progression (TTTP), to avoid confounding by post-progression therapy.…”
Section: Ongoing Trials Of Immunotherapy In Intermediate Stage Hccmentioning
confidence: 99%